Albet, Abel (ed.); Monk, Janice; Prats Ferret, Maria y Veleda da Silva, Susana M. (2019). Maria Dolors Garcia Ramon: Geografía y género, disidencia e innovación - Baylina, Mireia (Documents d'Anàlisi Geogràfica, 2019)
Albet, Abel (ed.); Monk, Janice; Prats Ferret, Maria y Veleda da Silva, Susana M. (2019) Maria Dolors Garcia Ramon: Geografía y género, disidencia e innovación Barcelona: Icària, 286 p. Espacios Críticos, 13 ISBN 978-84-9888-836-2